ANALISIS EFEKTIVITAS POTENSI PENERIMAAN PAJAK HOTEL DAN RESTORAN, SERTA PAJAK AIR TANAH TERHADAP PENDAPATAN ASLI DAERAH KOTA TANGERANG DI DINAS PENGELOLAAN KEUANGAN DAERAH (DPKD) KOTA TANGERANG - Yustiani, Revi (COMPETITIVE, 2021)
REVI YUSTIANI. Effectiveness and Contribution of Hotel and Restaurant Taxes, as well as the Tangerang City Groundwater Tax in the Tangerang City DPKD for the 2015-2017 Period. Under the guidance of Mrs. Siti Maryama, S.E., M.M.Local Original Revenue becomes very important because as a source of funding for the Regional Government which can be used as a benchmark in the implementation of regional autonomy and is one component of regional revenue sources, for example local income is the Hotel and Restaurant Tax, and Groundwater Tax. The purpose of this study was to determine the level of effectiveness of hotel and restaurant tax collection and groundwater tax in the city of Tangerang during 2015-2017 and to determine the contribution made by the hotel and restaurant tax and groundwater tax on the Local Original Revenue of the City of Tangerang during 2015- 2017. The data used in this study are secondary data with qualitative methods that refer to information collected from existing sources. Data analysis method used is descriptive analysis. Based on the results of the analysis, the level of effectiveness of hotel and restaurant taxes, as well as the Tangerang City groundwater tax during 2015-2017 was very effective and the contribution of hotel and restaurant tax revenue and groundwater tax on the Tangerang City's Local Original Revenues during 2015-2017 was very less.Keywords : effectiveness, contributions, hotel tax, restaurant tax, groundwater tax, local original revenue.